STUDIES ON THE VALUE OF COCOA HUSK IN THE NUTRITION OF COCKERELS (1988)
Four studies were carried out to determine the nutritive value of cocoa husk in cockerel rations. The parameters measured included performance and carcass characteristics, nutrient utilisation, histological studies, serum metabolites and economy of feed conversion. In the first study, the four main by-products from the cocoa industry (cocoa shell, cake, dust and husk) were chemically evaluated and their metabolisable energy values determined. Cocoa cake was found to contain the highest amount of crude protein while the crude fibre was highest in cocoa husk. Cocoa husk which also contained the highest amount of ash had the lowest content of theobromine. However, cocoa shell had a higher metabolisable energy value than cocoa husk. The high mineral content and low level of theobromine in cocoa husk coupled with its availability confirmed its advantages as an animal feed over the other cocoa by-products. In the second study, the wheat offal in the cockerel rations in both the starter and finisher phases was replaced with cocoa husk at 0, 25, 50, 75 and 100% levels in a twenty week study. In both phases, body weight gain decreased progressively with increasing dietary level of cocoa husk. The depression in growth rate was attributed to the high fibre Content of cocoa husk. The mean values of bodyweight gain in the starter phase were statistically significant (P<0.05) from each other. At the end of the starter phase, however, best results of average daily gain and efficiency of feed utilisation were obtained on birds fed the diet in which 25% of wheat offal was replaced with cocoa husk. This represents about 7% of cocoa husk in the ration for the starter phase. For the finisher phase, best results of < average daily gain, efficiency of feed utilisation and dressing out percentage among the cocoa husk diets were also obtained on birds fed the finisher diet in which 25% of wheat offal was replaced with cocoa husk. In addition, the lowest feed cost/kg liveweight of N4.89 was obtained on this diet which represented about 6% of cocoa husk in the finisher ration. The third study focused on the replacement of groundnut cake (GNC) in the cocoa husk based rations with palm kernel cake (PKC) at 0, 33, 66 and 100% levels in a sixteen week study. At the end of the starter phase; best results of average daily gain and efficiency of feed utilisation were observed on the birds fed cocoa husk diet in which 33% of the protein of the GNC was replaced with that of PKC. Average daily gain decreased with increasing levels of PKC in the diet. The protein intake in the starter phase also decreased with increasing level of fibre in the diet. The results of the performance of the cockerels in the finisher phase were not statistically different (P>0.05) from one another. However, best results of efficiency of feed utilisation and lowest mortality in the finisher phase were obtained on the birds fed cocoa husk diet in which the GNC was completely replaced with PKC. Compare with the result obtained on the control diet, the highest dressing percentage was also obtained on the diet without GNC. The histological changes noticed in the brain, liver and kidney tissues in all the treatments indicated chronic theobromine poisoning. Finally in this study, 20% and 37% levels of PKC were recommended in the cocoa husk based rations for the starter and finisher phases respectively. In the last study, cocoa husk was treated with the alkaline cocoa pod husk ash in order to improve it's digestibility. The treated cocoa husk (TCH) was mixed with the starter and finisher diets of cockerels in a study which lasted for sixteen weeks. The mean values of daily feed intake in the starter phase were statistically different (P< 0.05). The best results of bodyweight gain and protein utilisation were obtained on birds fed diets with 14% and 20% TCH in the starter and finisher phases respectively. The higher blood pH values obtained in the finisher phase could be due to the higher levels of treated cocoa husk (TCH) in the finisher diets. The highest dressing percentage was obtained on the diet containing 20% TCH while the best result of feed conversion was recorded on the diet containing 24% TCH. The results of this final study indicated that cockerels can tolerate higher Levels of TCH in the ration as compared to the lower levels of untreated cocoa husk recommended in the previous studies. Therefore, the levels of 14% and 20% TCH can be incorporated respectively in the starter and finisher diets of cockerels for optimal performance. However, as economy of feed conversion is of paramount importance to the poultry farmer, 24% of TCH in the finisher diet will be ideal.